Transmigration of permanent mandibular canines. Case report. - Shanmuhasuntharam, P.; Boon, L.C. (1991)
Transmigration is the migration of a tooth across the midline of the jaw. This phenomenon is found only in relation to the permanent mandibular canines. Two cases are reported. In both, the cause of this deviation was an odontome found in the site normally occupied by the mandibular canine. The literature on transmigration is reviewed.